Bridging the Perception-Experience Gap : Role of Tourism Marketing in Rebranding Poland - Szumska, Weronika; Lhotáková, Markéta, 1971-; Král, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates how tourism marketing can bridge the gap between pre-visit perceptions and post-visit experiences in Poland’s national rebranding. Based on theories of national branding, nation-brand equity, and the country-of-origin effect, it examines whether Poland’s promotional messages accurately reflect the experiences of international visitors. Then, Poland’s current tourism marketing strategies are reviewed. Following the theoretical research, the thesis analyses the results of the primary research, conducted to empirically evaluate the perception-experience gap. Using a mixed-methods design-quantitative gap analysis via the Holiday Satisfaction (HOLSAT) model, qualitative 4Q analysis of open-ended responses, and identification of Memorable Tourist Experiences (MTEs)-the study surveys German, Czech, and Italian travelers. Results show that tourists consistently underestimate Poland’s diverse attractions, warm hospitality, commitment to sustainability, and modern infrastructure; in these areas, actual visits significantly exceed expectations. By contrast, the promise of exceptional affordability exhibits a small negative gap, indicating that marketing may overstate Poland’s low-cost appeal. Stereotypes about safety risks, geopolitical instability, and social conservatism are largely disproven by visitor accounts. The thesis concludes that Polish tourism marketing should recalibrate its messaging—shifting from “budget” to “value,” showing authentic diversity, and directly countering outdated clichés to better align promotional narratives with today’s realities. These findings advance the understanding of how national branding strategies influence, and must adapt to, real-world tourist experiences.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses